Economic Order Quantity as a Quantitative Approach for Transaction Optimization in Community Economic Systems - Bunga Berlian; Yeni Budiawati; Johan Setiawan; Setiawan Sariyoga (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
Small and Medium Enterprises (SMEs) in the food processing sector often face challenges in managing raw material inventories efficiently, which can affect operational sustainability. This study aims to analyze inventory control of sweet potato procurement in a local SME producing processed food. Data were collected through interviews with three key informants (owner, production supervisor, and procurement staff), direct observation of raw material handling, and documentation of purchasing records, complemented by literature review. A descriptive quantitative approach was applied using calculations of Safety Stock, Minimum and Maximum Inventory Levels, Reorder Point, and Economic Order Quantity (EOQ). Results indicate that the optimal inventory range lies between 5,160 kg (minimum) and 6,420 kg (maximum). The EOQ method suggests an ideal order size of 732.04 kg per cycle, reducing annual inventory costs to IDR 464,787, which is lower than conventional ordering practices. Efficiency of inventory control was recorded at 10.19%, highlighting the need for structured methods to improve effectiveness. The findings demonstrate that systematic inventory management can minimize storage and ordering costs, prevent shortages or excess stock, and enhance operational efficiency. This research contributes to strengthening inventory management practices in SMEs engaged in local food processing.